PROBLEMATIKA KEPEMILIKAN MEREK AYAM GORENG SUHARTI : The Problamtics of Ownership of Ayam Goreng Suharti Trademark - Levinda Putri; Rr. Aline Gratika Nugrahani (Reformasi Hukum Trisakti, 2026)
Disputes over trademark ownership often arise from business development, particularly in culinary businesses that are inherited or managed by more than one party. One example that has generated legal debate concerns the ownership of the trademarks Ayam Goreng Suharti and Ayam Goreng Ny. Suharti. Both trademarks use the same identifying element, namely the name “Suharti,” causing public confusion and raising questions regarding the lawful trademark owner under statutory regulations, as both trademarks are registered. This study examines the ownership of the two trademarks based on Law Number 20 of 2016 on Trademarks and Geographical Indications. The research employs a legal research method with a statutory approach and qualitative analysis. The results show that trademark ownership depends on the first to file principle. Accordingly, the party entitled to use the name “Suharti” as a trademark is Suharti and Bambang Sachlan Pratohardjo, who registered the “Suharti” trademark in 1992, while the “Ny. Suharti” trademark was registered in 2021. Under Law Number 20 of 2016, only the trademark registered first is accepted and protected. Divorce or the dissolution of a business partnership does not justify the registration of trademarks that fail to meet legal requirements.